Ultrastructural and Cytotoxic Effects of Metarhizium robertsii Infection on Rhipicephalus microplus Hemocytes - Fiorotti, Jéssica; Menna-Barreto, Rubem Figueiredo Sadok; Gôlo, Patrícia Silva; Coutinho-Rodrigues, Caio Junior Balduino; Bitencourt, Ricardo Oliveira Barbosa; Spadacci-Morena, Diva Denelle; Angelo, Isabele da Costa; Bittencourt, Vânia Rita Elias Pinheiro (Frontiers in Physiology, 2019)
Metarhizium is an entomopathogenic fungus widely employed in the biological control of arthropods. Hemocytes present in the hemolymph of invertebrates are the cells involved in the immune response of arthropods. Despite this, knowledge about Rhipicephalus microplus hemocytes morphological aspects as well as their role in response to the fungal infection is scarce. The present study aimed to analyze the hemocytes of R. microplus females after Metarhizium robertsii infection, using light and electron microscopy approaches associated with the cytotoxicity evaluation. Five types of hemocytes (prohemocytes, spherulocytes, plasmatocytes, granulocytes, and oenocytoids) were described in the hemolymph of uninfected ticks, while only prohemocytes, granulocytes, and plasmatocytes were observed in fungus-infected tick females. Twenty-four hour after the fungal infection, only granulocytes and plasmatocytes were detected in the transmission electron microscopy analysis. Hemocytes from fungus-infected tick females showed several cytoplasmic vacuoles with different electron densities, and lipid droplets in close contact to low electron density vacuoles, as well as the formation of autophagosomes and subcellular material in different stages of degradation could also be observed. M. robertsii propagules were more toxic to tick hemocytes in the highest concentration tested (1.0 × 108 conidia mL -1). Interestingly, the lowest fungus concentration did not affect significantly the cell viability. Microanalysis showed that cells granules from fungus-infected and uninfected ticks had similar composition. This study addressed the first report of fungal cytotoxicity analyzing ultrastructural effects on hemocytes of R. microplus infected with entomopathogenic fungi. These results open new perspectives for the comprehension of ticks physiology and pathology, allowing the identification of new targets for the biological control.